ANALISIS PENGARUH KUALITAS PELAYANAN DAN INOVASI ADMINISTRASI TERHADAP KEPUASAN PESERTA DIDIK DENGAN CITRA SEKOLAH SEBAGAI VARIABEL INTERVENING PADA SMA TRISULA GUNUNG PUTRI, BOGOR - Miladi, Muhammad Miladi; Ahmadi, Slamet Ahmadi (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study aims to analyze the influence of Service Quality (SQ) and Administrative Innovation (AI) on Student Satisfaction (SS), with School Image (SI) as a mediating variable, at SMA Trisula Gunung Putri, Bogor. The main problem is the shift in public preferences from private schools to public schools or Islamic boarding schools, which require private schools to increase competitiveness. This quantitative research uses the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The sample consisted of 69 respondents selected from a total of 215 students through a simple random sampling technique. The results of the study show that Administrative Innovation and School Image significantly affect Student Satisfaction. Service Quality and Administrative Innovation also significantly affect the image of the School. A crucial finding is that Citra Sekolah fully mediates the relationship between Service Quality and Student Satisfaction, as well as mediates part of the relationship between Administrative Innovation and Student Satisfaction. It confirms that improved administrative services and innovations can improve the image and increase student satisfaction, which ultimately strengthens the competitiveness of private schools.